PENGARUH PEMANASAN DALAM BENTUK PERMAINAN TERHADAP EFEKTIVITAS PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (STUDI PADA SISWA KELAS X SMKN 1 DLANGGU MOJOKERTO) - BACHARUDIN YUSUF, WILLYS (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Education is a requirement that is not less important to the needs of others. One is physical, sport and health education. To create an exciting learning model for students is not easy, needs to be cautious the teacher in determining and implementing appropriate learning model that suits characteristics of the lesson given eventually creating effective learning process. In learning physical, sported and health education, warming up has very important role for the student, before entering the main learning activities. Therefore, exciting warming up can be packed on the game. The purpose of this study is to determine the effect of warming up in the form of games on the effectiveness of learning process of physical, sport and health education in the grader of SMKN 1 Dlanggu and how much is the influence. This research is an experiment with descriptive quantitative approach. The subjects in this study consisting of 68 students, which are of 36 students of class TKJ 10-3 as the experimental group and 32 students of class TKJ 10-2 as a control group. Sampling techniques using random cluster sampling. The instrument uses a questionnaire FCE. For data analysis using the t test or t test (independent). Based on the results of a calculation is known that the value of tcount 5,072 > 2,000 ttable with significance level of 0.05. While the magnitude of the effect is 4%. Keywords: Warming Up In The Form Of Games, Effectiveness Physical, Sport and Health Education Learning Proces